FREQUENCY OF ASSOCIATED WITH TEMPOROMANDIBULAR DYSFUNCTION DURING THE COVID-19 PANDEMIC - Barreto, Bruna Caroline Tomé (2023)
Objective: the purpose of this study is to determine the frequency of symptoms associated with temporomandibular disorders during the COVID-19 pandemic and to investigate the relationship between the appearance or worsening of TMD symptoms and the feelings of tension after the onset of the pandemic. Materials and Methods: this cross-sectional observational study collected information using an electronic questionnaire on the Google Forms platform from volunteers throughout the country over a period of around four months, regarding TMD symptoms from the beginning of the pandemic. Results: descriptive statistical analyses and Fisher’s exact test were applied to the 329 questionnaires collected, which had a mean age of 38 years (±13 years), with 122 men and 207 women respondents. The habit of squeezing and/or grinding the teeth was the most frequently reported symptom, while difficulty moving the mandible sideways was the least frequent. Fischer’s exact test revealed a statistically significant association (p<0.001) between the appearance or worsening of TMD symptoms and the onset or worsening of feelings of tension after the onset of the pandemic in all the items compared. Conclusion: the study found that less than half of the sample developed or worsened the TMD condition during the COVID-19 pandemic, and there was a positive association between the proposed symptoms.